School Principal Leadership in Enhancing Teacher Competence: A Qualitative Case Study in Merauke Secondary Schools - Erny, Erny (Jurnal Pendidikan Karakter, 2025)
The quality of education is closely tied to the professional competencies of teachers, which in turn are influenced by the effectiveness of school leadership. While numerous studies have examined the role of principals in enhancing teacher performance, limited research has explored the contextual dynamics of leadership practices in Indonesian secondary schools, particularly in less-represented regions such as Merauke. This study investigates how principals at SMP IT Lukman Al Hakim and SMP Muhammadiyah Merauke employ leadership strategies to foster teacher professional development, with a particular emphasis on pedagogical, professional, and technological competencies. A qualitative descriptive design was adopted, involving in-depth interviews, document analysis, and observations with school principals, teachers, and administrative staff. Data were analyzed thematically to identify patterns of leadership practices, challenges encountered, and strategies for overcoming barriers. The findings reveal that both schools implement transformational leadership, albeit with different emphases. SMP IT prioritizes inclusive collaboration and reflective supervision, while SMP Muhammadiyah focuses on curriculum innovation and digital integration. Despite positive impacts, challenges persist, including limited time for continuous professional development, teacher readiness in adopting digital tools, and structural constraints within school management. The study concludes that leadership, when adaptive and contextually grounded, significantly enhances teacher competence and indirectly improves student outcomes. This research contributes to the literature by providing comparative insights into leadership practices in Indonesian junior secondary schools, offering both theoretical and practical implications for educational leadership and policy.